(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study traces the understanding of the Tobu Christian community to the trinity and the triune God.This study emerges as an effort to contextualize Christianity’s understanding of the Triune God. And the Tobu people who once held the Halaik belief. Tobu society has accepted Christ but there is a dualism of belief about God. The triune God is still understood in the perspective of tribal religion. It is also undeniable that Tertullian, Origen, and Arius, Sebelis and Karl Barth have different thoughts about the Trinity. Because of that the writer recommends transformative contextualization to the Tobu community. In order to search for this understanding, the author uses descriptive qualitative method. The author tries to deepen the understanding of the Tobu community with interviews and observations. This study tries to interpret the symbols and myths that develop in the Tobu community. So the authors offer an understanding of the trinity in accordance with the thoughts given by Nuban Timo namely God’s Triple Self Repetition Model. God in the three persons would be thrice himself. Persons would be nothing more than the triple repetition of God. The person dose away with the interpersonal concept of relations as well. Moreover the number three becomes incomprehensible. The Father, the Son, and the Holy Spirit are always present together and doing the same work (creation, salvation, and redemption) each with the roles and tasks that are its portion to make the work come true.